2019
DOI: 10.3389/fendo.2019.00630
|View full text |Cite
|
Sign up to set email alerts
|

Adipsic Diabetes Insipidus—The Challenging Combination of Polyuria and Adipsia: A Case Report and Review of Literature

Abstract: Adipsic Diabetes Insipidus is a rare hypothalamic disorder characterized by a loss of thirst in response to hypernatraemia accompanied by diabetes insipidus. These occur secondary to a congregation of defects in the homeostatic mechanisms of water balance. A 27-year old Chinese female presented with Adipsic Diabetes Insipidus after cerebral arteriovenous malformation (AVM) surgery. Initial diagnosis and management was extremely challenging. Long term management required a careful interplay between low dose vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Notably, the incidence of CDI (81.4%) in our study was higher than that reported in children undergoing HD ( 3 ). We found that one-third of our patients with CDI presented with adipsia, which may indicate damage to osmoregulatory and thirst perception pathways comprising the hypothalamic nuclei, namely the median preoptic nucleus (MnPO) and organum-vasculosum lamina terminalis (OVLT) ( 26 , 27 ). Comprehensive and coherent management approaches are required for ADI, including desmopressin, compensatory fluid intake, daily weighing, and frequent serum sodium monitoring ( 15 , 26 ).…”
Section: Discussionmentioning
confidence: 93%
“…Notably, the incidence of CDI (81.4%) in our study was higher than that reported in children undergoing HD ( 3 ). We found that one-third of our patients with CDI presented with adipsia, which may indicate damage to osmoregulatory and thirst perception pathways comprising the hypothalamic nuclei, namely the median preoptic nucleus (MnPO) and organum-vasculosum lamina terminalis (OVLT) ( 26 , 27 ). Comprehensive and coherent management approaches are required for ADI, including desmopressin, compensatory fluid intake, daily weighing, and frequent serum sodium monitoring ( 15 , 26 ).…”
Section: Discussionmentioning
confidence: 93%
“…The diagnosis can be confirmed by the normalization of these abnormalities by desmopressin administration, as in the present patient. 11,13 CDI is commonly caused by neoplastic or infiltrative hypothalamic lesions, traumatic brain injury, neurosurgery, or autoimmune destruction of the posterior lobe of the pituitary. 2,[14][15][16] Pituitary MRI is used for the diagnosis and to determine the etiology of CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Euvolemic hypernatremia is a feature of central diabetes insipidus (low ADH secretion) occurring in primary or metastatic tumors of the pituitary gland or hypothalamus, after ablative surgery of these tumors or secondary to whole brain radiation in patients with central nervous system lymphomas or brain tumors [22,23]. In some of these patients, lesions involving hypothalamic osmoreceptors may lead to reduced thirst and decreased water intake with severe dehydration, a dangerous and rare syndrome called adipsic diabetes insipidus [24,25]. Some chemotherapeutics may interfere with the renal action of ADH by inducing nephrogenic diabetes insipidus; the most commonly involved are amphotericin B, ifosfamide, platinum derivatives [26].…”
Section: Causes Of Hypernatremia In Cancermentioning
confidence: 99%